KORELASI KINERJA GURU DAN MINAT BELAJAR DENGAN PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN MATEMATIKA - Musdalifah, Sri; Ramli, Muhammad; Mardyawati, Mardyawati; Mania, Sitti; Mardhiah, Mardhiah (Idaarah: Jurnal Manajemen Pendidikan, 2024)
The level of learning achievement is influenced by several indicators, including teacher performance and interest in learning. This research is useful in proving that there is a correlation between teacher performance and interest in learning in the same way as students' learning achievement in mathematics subjects at SMP Muhammadiyah 6 Makassar. This type of quantitative field research research has a research sample of 46 students at SMP Muhammadiyah 6 Makassar. The results of the research show a correlation between teacher performance and interest in learning in the same way as learning achievement at SMP Muhammadiyah 6 Makassar. This is based on the results of the inferential statistical hypothesis test obtained sig. F change <ɑ(0.004<0.05) means that there is a correlation between teacher performance and interest in learning on student learning achievement for subjects that can be accepted or proven to be correct. It is hoped that the implications of the research results will become reference material for similar researchers. More than that, it is desirable that there be further research regarding aspects that influence teacher performance, interest in learning, and student learning achievement from a broader perspective.